Jamur MikorizaVesikularArbuskular (MVA) pada Rhizosfer Tanaman Langsat (Lansium domesticumCorr.) di Lahan Gambut - Siti Khotimah, Luqman, Riza Linda, (Universitas Tanjungpura, 2015)
The Vesicular Arbuscular Mycorrhizal (VAM) fungi are a mutualistic symbiosis between the fungi and the plant root. The VAM fungi are capable of improving the plant growth. Information on the types of the MVA fungi on the roots of the langsat (L. domesticum) in peatsoil is yet to be known. This research aimed to find out the types of the MVA fungi and the level of infection on the roots of langsat (L. domesticum). The research was carried our at the Laboratory of Microbiology of the Faculty of Mathematics and Natural Sciences, Tanjungpura University from February to April 2015. The analysis of soil samples were conducted in the Laboratory of Chemistry and Soil Fertility of the Faculty of Agriculture, Tanjungpura University. The isolation of soil samples used the wet-sieving and decanting technique followed by the centrifugation technique. The research found a total of 232 spores of MVA fungi, consisting of the genera Glomus (10 types), Paraglomus (3 types) and Acaulospora (3 types). The results of observation on the root preparations found the structures of MVA fungi such as spores, hyphae and vesicles with the percentage of root infection at 41%, which fell into to the intermediate category.